2013
DOI: 10.1016/j.jams.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Management of Balance Impairment in a Patient with Bipolar Disorder

Abstract: A case is reported of unexplained unilateral thigh muscle atrophy and frequent falling with poor response to conventional conservative treatments in a patient with bipolar disorder who self-selected acupuncture treatment as a last resort. The patient experienced gradual improvements in lower extremity weakness and fewer falls during the 8-month treatment. No adverse event or aggravation of the bipolar disorder was observed. These outcomes suggest that acupuncture may be a feasible adjunct for reducing falling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It was reported that TGA might be effective for unexplained autoimmune disease, psychosomatic illness, depression and anxiety, chest tightness and pressure, insomnia, cognitive dysfunction, chronic fatigue syndrome, chronic pains in multiple sites from neuromuscular conditions, shoulder stiffness, and imbalance of sympathetic and parasympathetic systems though it needs further validation. 17 , 18 , 20 , 21 , 22…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was reported that TGA might be effective for unexplained autoimmune disease, psychosomatic illness, depression and anxiety, chest tightness and pressure, insomnia, cognitive dysfunction, chronic fatigue syndrome, chronic pains in multiple sites from neuromuscular conditions, shoulder stiffness, and imbalance of sympathetic and parasympathetic systems though it needs further validation. 17 , 18 , 20 , 21 , 22…”
Section: Discussionmentioning
confidence: 99%
“…There are several rules for selecting six (or five) Sasang type-specific points of TGA 18 , 21 , 22 , 32 ; however, the detailed rationale was not explained in full till now. Three type-specific points ( Table 1 ) are selected for patient’s Sasang type and another three supplementary points (ST36, LI4, and LI11) are also combined to enrich the qi circulation during the TGA treatment.…”
Section: Sasang Type Differentiation and Type-specific Acupuncture Trmentioning
confidence: 99%
See 3 more Smart Citations